Preventing Bacterial Contamination of Breast Implants Using Infection Mitigation Techniques: An In Vitro Study - Chow, Oliver; Hu, Helen; Lajevardi, Sepehr; Deva, Anand K; Atkinson, Richard (Aesthetic surgery journal, 2024)
Bacterial contamination of implants has been linked to the formation of biofilm and subsequent infection, capsular contracture and Breast Implant Associated Anaplastic Large Cell Lymphoma. Reducing contamination during implant insertion should therefore reduce biofilm formation disease sequelae. Compare levels of contamination between preventative techniques. A model to simulate the passage of implants through a skin incision was designed using a sterile textured polyvinyl plastic sheet contaminated with Staphylococcus epidermidis. Implants were subject to infection mitigation techniques and passed through the incision, then placed onto horse blood agar plates and incubated for 24 hours.Part 2 of the study applied the same contamination to human abdominal wall specimens) 5 cm incision was made through skin and fat, then implants were passed and levels of contamination were measured as described. Smooth implants were seen to grow a mean of 95CFU (approximately 1CFU/cm2) and textured implants grew 86CFU (also approximately 1CFU/cm2). CFU counts were analysed using the Mann Whitney U test which showed no significant difference between implant types (P < 0.05). Significant difference shown using independent samples T-tests. The dependent variable techniques were then compared as groups using one way ANOVA and this also showed a significant reduction when compared to the control group (p < 0.01). This study has shown in-vitro the effectiveness of antiseptic rinse and skin/implant barrier techniques to reduce bacterial contamination of breast implants at the time of insertion.